Quantum Theory of Molecular Communications in Nanomedicine - Nieto-Chaupis, Huber (2020)
It is well-known that Nanomedicine will use all those available techniques of Nanotechnology to alleviate and surpass critic scenarios of diseases by the which current Medicine might be limited. In this paper, we explore possible scenarios of nano cargo delivering nanoparticles aimed to reach a cell or tissue. The theory of Quantum Mechanics to estimate the probabilities of releasing and arriving of nanoparticles to their target. The simulations have shown that electrical interactions is a noise that minimizes the central role of nanoparticles, and might cause the fail of an event of Targeting Drug Delivery (TDD in short), for example.